Stress State of Disk Tool Attachment Points on Tetrahedral Prisms between Axial Bits; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Khoreshok A. A. Aleksey Alekseevich; Mametyev L. E.; Borisov A. Y.; Vorobyev A. V. Aleksey Vasilievich (Designing and Modelling of Machines and Mechanisms, 2015)
Title screen